The interplay of subsidiary performance and cultural distance in international downsizing decisions - Miriam Flickinger; Miriam Zschoche (Schmalenbach Journal of Business Research (SBUR), 2023)
Existing literature has primarily identified financial and/or strategic considerations as drivers of international downsizing decisions. A subsidiary's performance seems to have a superior meaning among those considerations. Cultural distance is also an important factor, although its influence on downsizing is ambiguous: It increases coordination costs and, hence, lowers performance; however, cultural distance might also entail benefits of diversity and diversification. We challenge prior perspectives on the role of cultural distance in international downsizing decisions by showing that cultural distance also bears influences beyond efficiency considerations. Using insights from social identity and self-categorization theory, we argue that cultural distance influences how decision-makers interpret the efficiency of the subsidiary in terms of its performance. We expect that the lower the cultural distance, the more positively performance outcomes will be interpreted, leading to less workforce downsizing in a culturally proximate subsidiary as compared to one that is culturally more distant. Results of our large-scale empirical analysis of more than 14,000 downsizing decisions of German MNCs throughout 60 industries and across 54 host countries support our predictions.
Keywords: 650; Subsidiary management; Cultural distance; Social identity theory; Performance; Employee dismissal